2013
DOI: 10.1590/s1415-47572013000100004
|View full text |Cite
|
Sign up to set email alerts
|

Association of killer cell immunoglobulin-like receptor polymorphisms with chronic hepatitis C and responses to therapy in Brazil

Abstract: Soroprevalence for Hepatitis C virus is reported as 2.12% in Northern Brazil, with about 50% of the patients exhibiting a sustained virological response (SVR). Aiming to associate polymorphisms in Killer Cell Immunoglobulin-like Receptors (KIR) with chronic hepatitis C and therapy responses we investigated 125 chronic patients and 345 controls. Additionally, 48 ancestry markers were genotyped to control for population stratification. The frequency of the KIR2DL2 and KIR2DL2+HLA-CAsp80 gene and ligand was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…The higher representation of KIR2DS2 and KIR2DL2 genes among our chronically HCV-infected male patients than in healthy controls is in keeping with the favorable effect of the KIR2DL3/KIR2DL3+ C1C1 genotype on the elimination of the virus [13][14][15], because KIR2DS2/KIR2DL2 and KIR2DL3 are mutually exclusive in the centromeric part of the KIR locus [8]. It is also in accord with data published recently by de Vasconcelos et al [28] who observed an association of KIR2DL2 and KIR2DS2 with chronic HCV infection, but they did not give the proportion of males and females in their sample. Interestingly, a ÀKIR2DS2/KIR2DL2À C1C1 (but not KIR2DS2/KIR2DL2 alone) genotype has been recently described as a risk factor for an earlier age at onset of hepatocellular carcinoma in hepatitis B virus infection in Chinese, but, again, There was no statistically significant difference between studied groups (p = 0.8851).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The higher representation of KIR2DS2 and KIR2DL2 genes among our chronically HCV-infected male patients than in healthy controls is in keeping with the favorable effect of the KIR2DL3/KIR2DL3+ C1C1 genotype on the elimination of the virus [13][14][15], because KIR2DS2/KIR2DL2 and KIR2DL3 are mutually exclusive in the centromeric part of the KIR locus [8]. It is also in accord with data published recently by de Vasconcelos et al [28] who observed an association of KIR2DL2 and KIR2DS2 with chronic HCV infection, but they did not give the proportion of males and females in their sample. Interestingly, a ÀKIR2DS2/KIR2DL2À C1C1 (but not KIR2DS2/KIR2DL2 alone) genotype has been recently described as a risk factor for an earlier age at onset of hepatocellular carcinoma in hepatitis B virus infection in Chinese, but, again, There was no statistically significant difference between studied groups (p = 0.8851).…”
Section: Discussionsupporting
confidence: 92%
“…In the latter study, the co-distribution of KIR2DS3 and KIR2DS5 was not tested; their data are, however, somewhat contradictory to ours, where the presence of KIR2DS3 rather than KIR2DS5 favored a lower viremia in infected individuals. The association of KIR2DS3 (alone and together with KIR2DL2 and KIR2DS2) with chronic hepatitis C was also described recently by de Vasconcelos et al [28]. In HCV-related hepatocellular carcinoma the presence of KIR2DS5 gene was associated with markedly longer overall survival [32].…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, there was loss of the KIR2DS3 allele. This allele has been found to be associated with chronicity for both hepatitis B and hepatitis C and is also a susceptibility factor for Ebola virus . Furthermore, it was absent from the majority of KIR haplotypes identified in other Amerinidian tribes studied, which have haplotypes containing KIR2DS5 rather than KIR2DS3 .…”
Section: Kirmentioning
confidence: 90%
“…Therefore the mechanism underlying this association may be complex. The absence of a KIR2DL3:group 1 HLA‐C interaction appears to be detrimental to HCV outcome in a number of different populations .…”
Section: Resolution Of Hcvmentioning
confidence: 99%